Effects of CuO film thickness on electrical properties of CuO/ZnO and CuO/ZnS hetero-junctions. (December 2015) - Chabane, L.; Zebbar, N.; Zeggar, M. Lamri; Aida, M.S.; Kechouane, M.; Trari, M.
Abstract: It is known that the quality of the diode and the transport of the charge carriers across the junction may be greatly influenced by the quality of the interface, and depends on the crystallinity of thin layers. In this work, we have prepared the p-CuO/n-ZnO and p-CuO/n-ZnS hetero-junctions by ultrasonic spray pyrolysis at 300 °C under atmospheric pressure. We have investigated the influence of the thickness of CuO film on the electrical properties of the hetero-junctions. The X-ray diffraction indicates that both the CuO and ZnO thin films grow according to polycrystalline nature while ZnS films show a quasi-amorphous nature. The current voltage temperature ( I – V – T ) and capacitance voltage ( C – V ) characteristics reveal that CuO/ZnS is an abrupt junction, whereas the data of CuO/ZnO hetero-junctions suggest that the potential barrier heights are spatially non-uniform (junction not abrupt). The electrical behavior of the junction is strongly affected by the defect state distribution at the hetero-interface. The recombination process involving the interface states predominates at low forward bias ( V <0.5 V), whereas trap assisted multi-step tunneling capture emission (MTCE) prevails in the higher bias region ( V >0.5 V) on the thin CuO side. The junction parameters (ideality factor, rectification ratio, built in potential etc…) are of the same order of magnitude for both heterojunction diodes i.e. ZnO/CuO and ZnS/CuO. Highlights: ZnO, ZnS and CuO films have been deposited by ultrasonic spray pyrolysis. CuO/ZnO and CuO/ZnS hetero-junction showed a rectifying behavior. CuO/ZnS hetero-junction is an abrupt junction unlike CuO/ZnO. The transport mechanism is controlled by the interface states and defects in CuO.